Isolation by oceanic distance and spatial genetic structure in an overharvested international fishery. Issue 11 (18th September 2017) - Truelove, Nathan K.; Box, Stephen J.; Aiken, Karl A.; Blythe‐Mallett, Azra; Boman, Erik M.; Booker, Catherine J.; Byfield, Tamsen T.; Cox, Courtney E.; Davis, Martha H.; Delgado, Gabriel A.; Glazer, Bob A.; Griffiths, Sarah M.; et al.
Abstract: Aim: A detailed understanding of spatial genetic structure (SGS) and the factors driving contemporary patterns of gene flow and genetic diversity are fundamental for developing conservation and management plans for marine fisheries. We performed a detailed study of SGS and genetic diversity throughout the overharvested queen conch ( Lobatus gigas ) fishery. Caribbean countries were presented as major populations to examine transboundary patterns of population differentiation. Location: Nineteen locations in the greater Caribbean from Anguilla, the Bahamas, Belize, Caribbean Netherlands, Honduras, Jamaica, Mexico, Turks and Caicos, and the USA. Methods: We genotyped 643 individuals with nine microsatellites. Population genetic and multivariate analyses characterized SGS. We tested the alternate hypotheses: (1) SGS is randomly distributed in space or (2) pairwise genetic structure among sites is correlated with oceanic distance (IBOD). Results: Our study found that L. gigas does not form a single panmictic population in the greater Caribbean. Significant levels of genetic differentiation were identified between Caribbean countries ( F CT = 0.011; p = .0001), within Caribbean countries ( F SC = 0.003; p = .001), and among sites irrespective of geographic location ( F ST = 0.013; p = .0001). Gene flow across the greater Caribbean was constrained by oceanic distance ( p = .0009; Mantel r = .40), which acted to isolate local populations. Main conclusions: Gene flow over the spatial scale of the entire Caribbean basin is constrained by oceanic distance, which may impede the natural recovery of overfished L. gigas populations. Our results suggest a careful blend of local and international management will be required to ensure long‐term sustainability for the species.